2021
DOI: 10.1080/1040841x.2021.1907740
|View full text |Cite
|
Sign up to set email alerts
|

Colonization ofHelicobacter pyloriin the oral cavity – an endless controversy?

Abstract: Helicobacter pylori is associated with chronic gastritis, gastric or duodenal ulcers, and gastric cancer. Since the oral cavity is the entry port and the first component of the gastrointestinal system, the oral cavity has been discussed as a potential reservoir of H. pylori. Accordingly, a potential oral-oral transmission route of H. pylori raises the question concerning whether close contact such as kissing or sharing a meal can cause the transmission of H. pylori. Therefore, this topic has been investigated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 96 publications
(148 reference statements)
0
28
0
1
Order By: Relevance
“…9 Helicobacter pylori has been detected as positive in oral samples using molecular methods, immunological methods or culture methods, and the oral cavity has been discussed as a potential reservoir of H. pylori. 10 The oral microbiota promotes the colonization of H. pylori through coaggregation, symbiotic biofilm formation, and endosymbiosis 11 ; however, whether H. pylori is resident or transient in the oral cavity must be clarified. Li et al 12 demonstrated that different oral community structures exist between H. pylori-positive and H. pylori-negative groups using high-throughput sequencing of saliva samples.…”
Section: Introductionmentioning
confidence: 99%
“…9 Helicobacter pylori has been detected as positive in oral samples using molecular methods, immunological methods or culture methods, and the oral cavity has been discussed as a potential reservoir of H. pylori. 10 The oral microbiota promotes the colonization of H. pylori through coaggregation, symbiotic biofilm formation, and endosymbiosis 11 ; however, whether H. pylori is resident or transient in the oral cavity must be clarified. Li et al 12 demonstrated that different oral community structures exist between H. pylori-positive and H. pylori-negative groups using high-throughput sequencing of saliva samples.…”
Section: Introductionmentioning
confidence: 99%
“…The coccoid form is a quiescent state of H. pylori in the oral cavity and could not be resurrected in the bacterial culture medium. In contrast, the spiral form of H. pylori in the stomach can be found ( Mao et al 2021 ). More importantly, the coccoid H. pylori trigger the alternations of the gastric tissues when they are gavaged into the stomach for two weeks ( Cellini et al 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity is as suitable for a H . pylori reservoir as the stomach in adults[ 18 ], as are inflamed teeth (pulp) in children[ 18 ], but this is still a controversial issue[ 15 , 35 , 50 ]. It remains unclear whether H .…”
Section: Reliable Dna Diagnosticsmentioning
confidence: 99%
“…It remains unclear whether H . pylori colonizes the oral cavity residentially, transiently, or at all[ 35 ]. Therefore, saliva and feces from 81 individuals were examined for the presence of H. pylori -specific DNA by simple and nested PCR.…”
Section: Reliable Dna Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation